Cobalt‐Based Metal–Organic Framework Nanoarrays as Bifunctional Oxygen Electrocatalysts for Rechargeable Zn‐Air Batteries. Issue 69 (30th October 2018) - Chen, Guangbo; Zhang, Jian; Wang, Faxing; Wang, Lanlan; Liao, Zhongquan; Zschech, Ehrenfried; Müllen, Klaus; Feng, Xinliang
Abstract: Owing to their high theoretical energy density, environmental benign character, and low cost, rechargeable Zn‐air batteries have emerged as an attractive energy technology. Unfortunately, their energy efficiency is seriously plagued by sluggish oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) that alternately occurs on air electrodes. Herein, we demonstrate Co‐based metal–organic framework (Co(bpdc)(H2 O)4 (bpdc=biphenyl −4, 4′‐dicarboxylic acid), Co‐MOF) arrays as novel bifunctional oxygen electrocatalysts. The Co‐MOF is in situ constructed on a three‐dimensional graphite foam (GF) through a hydrothermal reaction. In a 1 m KOH aqueous solution, the resultant Co‐MOF/GF exhibits an OER overpotential of only ≈220 mV at 10 mA cm −2, which is much lower than those for Ir/C and previously reported noble metal‐free electrocatalysts. In conjunction with its ORR half‐wave potential of 0.7 V (vs. RHE), the Co‐MOF/GF manifests a greatly decreased potential gap of ≈0.75 V in comparison with Pt/C‐Ir/C couple and previously reported bifunctional oxygen electrocatalysts. Furthermore, an assembled rechargeable zinc‐air battery using Co‐MOF electrocatalyst in an air electrode delivers a maximum power density of 86.2 mW cm −2 and superior charge–discharge performance. Microscopic, spectroscopic and electrochemical analyses prove that the initial Co‐MOF is transformed into Co‐oxyhydroxides during the OER and ORR process, which essentially serve as bifunctional active centers. Abstract : Array of hope : An approach for constructing Co‐based MOF arrays, which can efficiently serve as bifunctional oxygen electrocatalyst for rechargeable Zn‐air batteries, is reported. The CoOOH nanosheets in situ derived from the Co‐MOF arrays are confirmed to be bifunctional active centers for catalyzing the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR).